English Language Teaching Training Programme for the non-English Teachers of the Vavuniya and Mannar Districts in Sri Lanka: A Study - Shriganeshan, K. (Asian Studies International Journal Vol I, Issue No.1(December 2019): Pages 16-21 ©ICRD Publication, 2019)
When the war ended in 2009 Sri Lanka, the situation improved in the war-torn districts and many returnees arrived from abroad after some years of displacement. But they have to face a lot of challenges with regard to reintegration into local communities. Many children returning from Tamil Nadu received English lessons in Tamil Nadu and their English skills are more developed and the poor standard of English in Sri Lankan schools in Mannar and Vavuniya districts required more attention of the educationists of the districts. In order to support the development of English language skills in the education system in these districts Vavuniya Campus of the University of Jaffna, Sri Lanka took the task of training non-English teachers whose English language teaching skills need to be developed. A six-month programme to promote the English language skills of the teachers with the objectives of empowering the professional level of the teachers was introduced with the hope of enabling the non English teachers to be active in the classrooms with required knowledge of English. The paper will study qualitatively how the programme was conducted and how the proficiency level of the teachers was developed. It is noted to record the participants’ involvement during the course and to see whether the course was able to increase their level of proficiency in English and improve their standard of English with regard to communication skills and the teaching methodology.
Keywords: Proficiency; Professional level; Empowering; Participant’s involvement